Jalan Panjang Pemberitaan Terorisme di Indonesia Sejak Masa Kolonial Hingga Kini - John Nedy Kambang; Rahmi Surya Dewi; Ernita Arif (Jurnal Ranah Komunikasi, 2020)
The mass media, which has existed since Europeans entered Indonesia, has undergone many developments. The first printed media published by Europeans, Bataviasche Nouvelles, only contained information about the VOC government, trade, entertainment, auction advertisements and the history of the Dutch colony in the Indies. Also about the spread of Catholicism and Protestantism, and the development of the church in the Indies. In subsequent developments, various mass media began to appear, such as newspapers and magazines which were not only owned by the Dutch, but also made by indigenous people, such as Medan Prijaji, Otoesan Hindia and many others. The media continues to evolve to this day. Nothing has changed in the purpose of the media, from past to present, namely to convey information. However, the method of delivery and the content of the news seems much different. One of them is in delivering news about war and terrorism. During the Dutch era, news about war and terrorism was not reported clearly. Meanwhile, today the mass media seems to be divided into two functions, as a protector for government officials, and as a propagator. In reporting on terrorism, the media today are very open in reporting it. The arrests of members of terrorism in which the shooting were also broadcast live. There has been a shift in the pattern of media delivery from the Dutch colonial era to the Reformation Era, especially on sensitive issues such as terrorism. This article uses a combination of a narrative approach with a historical approach, in observing the development of the mass media in reporting on terrorism from the Dutch colonial era to the reform era today. The tendency of this research is historical, mixed with narratives built by figures who become sources of information. The methodology used in this article uses literature studies in the form of mass media archives as a data source, and is complemented by interviews from terrorism experts as sources to strengthen the analysis.